Camperdown hemoglobin associated with beta° thalassemia in a Brazilian child - Tania Regina Tozetto-Mendoza; Paulo Roberto Santos Ferreira; Nilcéia Maria Viviani; Dulcinéia Martins Albuquerque; Ivana Rizzi; João Targino de Araújo (Genetics and Molecular Biology, 2005)
We report the coexistence of Hb Camperdown [beta104 (G6) Arg -> Ser] and beta°-thalassemia [beta39 (Gln -> stop codon)] in a nine-month-old Brazilian boy. He had a relatively more severe hypochromic and microcytic anemia in comparison to his mother's beta-thalassemia trait. His Hb Camperdown heterozygous father was clinically and hematologically normal. To our knowledge, this is the first description of an association of beta°-thalassemia with Hb Camperdown.